Unpublished archaeological findings from the areas of Brčko and Bijeljina: a contribution to research of the past of Northeastern Bosnia - Imamović, Mersiha (Historical Thought, 2024)
This paper studies archaeological objects kept in the Museum of the Brčko District of Bosnia and Herzegovina, with the analysis of two accidentally discovered finds on the banks of the Sava River, in the area of Bijeljina. The objects, mostly metal, include axes and chisels, with a predominance of iron specimens, while one bronze axe stands out among them – Celtic, as well as a bronze key and a fragment of a key. The axe – Celtic dates back to the Bronze Age, while other objects can be placed in a wider time frame. The areas of Brčko and Bijeljina were inhabited during the prehisto ric and Roman periods, and the settlement of this area continued in the Middle Ages and in later times. The archaeological finds in question testify to the daily use of these objects throughout the mentioned periods.